Pengaruh Career Development, Work-Life Balance, Organization Climate dan Kepuasan Kerja Terhadap Turnover Intention Pegawai BPR Bhakti Daya Ekonomi Yogyakarta - Inayat Hanum Indriati; Ningrum Natalia (JEMBATAN, 2022)
The purpose of this study was to determine the effect of career development, work-life balance, organization climate and job satisfaction on employee turnover intention. The sample of this research is all employees of BPR Bhakti Daya Ekonomi Yogyakarta, totaling 50 people who were selected by population sampling technique. The method of collecting data is a questionnaire. The data analysis technique used multiple linear regression analysis. The results showed that (1) Career development had a negative effect on employee turnover intention; (2) Work-life balance has no significant effect on employee turnover intention; (3) Organizational climate has a negative effect on employees turnover intention; (4) Job satisfaction has a negative effect on employees turnover intention; (5) Career development, work-life balance, organizational climate and job satisfaction simultaneously have a significant effect on employee turnover intention.